The first identification of the benzenediazonium ion formation from a non-aminoazo dye, 1-phenylazo-2-hydroxynaphthalene (Sudan I) by microsomes of rat livers - Stiborová, M; Asfaw, B; Anzenbacher, P; Leseticky, L; Hodek, P (Cancer letters, 1988)
1-Phenylazo-2-hydroxynaphthalene (Sudan I) is converted by microsomal enzymes of rat livers in vitro to 5 products. Hepatic microsomes from 5,6-benzoflavone-treated rats are more effective for the metabolism of Sudan I than those from phenobarbital- or Sudan I alone-treated rats. Major products formed by microsomes are identified as the ring-hydroxyderivatives of benzene and naphthalene rings. The formation of the benzenediazonium ion evolved by oxidative splitting of the azo group of Sudan I by microsomal enzymes is also proved. The oxidative splitting of Sudan I by microsomal enzymes may be considered as the possible mechanism of the Sudan I activation to the ultimate carcinogen (benzenediazonium ion).
Keywords: jaterní mikrozomy; Coloring Agents; benzoflavony; Biotransformation; Microsomes, Liver; naftoly; edaravon; Antipyrine; Rats, Inbred Strains; krysa rodu Rattus; Diazonium Compounds; zvířata; chromatografie na tenké vrstvě; Benzoflavones; Naphthols; Male; Carcinogens; barvicí látky; karcinogeny; biotransformace; Rats; Chromatography, Thin Layer; diazoniové sloučeniny; Animals; Edaravone; fenazon; mužské pohlaví; inbrední kmeny potkanů